2020
DOI: 10.28956/gbd.736179
|View full text |Cite
|
Sign up to set email alerts
|

Çevri̇mi̇çi̇ Banka Karti Dolandiriciliği: Ri̇sk Faktörleri̇ni̇ Anlamada Ruti̇n Akti̇vi̇teler Yaklaşimi

Abstract: Banking cards, including credit cards, debit card, prepaid debit cards and ATM cards, have become the primary payment method in online transactions. However, this popularity boosted the Card-not-present (CNP) fraud victimization. Despite numerous studies exploring technological solutions to prevent CNP fraud, there is a shortage of theoretically informed research exploring the online lifestyle correlates of CNP. This study, which utilizes the dataset of Crime Survey for England and Wales 2014/2015, addresses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…While the former study indicated a rise in risky online activities, the latter revealed a lack of change in online behavioral patterns. Put together, the results of these two studies seem to underscore the influence of engaging in risky online activities on the likelihood of experiencing cyber victimization (Akdemir & Yenal, 2020;Holt & Bossler, 2013;Leukfeldt, 2014).…”
Section: Introductionmentioning
confidence: 76%
“…While the former study indicated a rise in risky online activities, the latter revealed a lack of change in online behavioral patterns. Put together, the results of these two studies seem to underscore the influence of engaging in risky online activities on the likelihood of experiencing cyber victimization (Akdemir & Yenal, 2020;Holt & Bossler, 2013;Leukfeldt, 2014).…”
Section: Introductionmentioning
confidence: 76%